Statistical atlases and computational models of the heart : atrial segmentation and LV quantification challenges : 9th International Workshop, STACOM 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Revised selected papers /: atrial segmentation and LV quantification challenges : 9th International Workshop, STACOM 2018, held in conjunction with MICCAI 2018, Granada, Spain, September 16, 2018, Revised selected papers. (2019) - Unknown
No abstract available